Molten salt oxidation and process analysis of anionic exchange resin in Na2CO3-K2CO3 melt. Issue 5 (4th May 2022) - Zheng, Yang-Hai; Xue, Yun; Yan, Yong-De; Wang, Xue-Ze; Ma, Fu-Qiu; Zhang, Mi-Lin; Yin, Tai-Qi; Kou, Zi-Qi; Bai, Hai-Yun; Liu, Jian-Peng
ABSTRACT: The oxidation characteristics of anionic exchange resins (AERs) during molten salt oxidation (MSO) were investigated in carbonate melt. The residue after MSO of AERs were carbon, which was confirmed by the X-ray diffraction (XRD) and Raman spectra. The remaining amount of salt-free residue after MSO was evaluated by destruction and removal efficiency (DRE), which indicates that 2 hours is a suitable oxidation time. The morphologies of the AERs after MSO were observed by scanning electron microscopy (SEM). The oxidation process of AERs in MSO was investigated by thermogravimetric analysis (TG) and Fourier Transform Infrared Spectrometer (FT-IR), which revealed that initial AERs, experienced four reaction stages in MSO: dehydration, thermal decomposition of functional groups, carbonization of styrene-divinylbenzene copolymer (ST-DVB), and gasification of carbon. The TG data proved that the presence of carbonate promotes the carbonization process of ST-DVB in AERs. The reason why salt catalyzes this stage had been proved to be that the carbonate captures the nitrogen-containing exhaust gas generated by the oxidation of the anion resin, and produces nitrate with catalytic oxidation ability, which catalyzes the oxidation of the resins effectively. This means that MSO will be an environmentally friendly and efficient method for catalytic oxidation of AERs.